Determination of phenolic contents of Red Chilli (Capsicum annuum) and Paddy Chilli (Capsicum frutescens) for pest resistance observation - Siti Norma, Azizan (Universiti Malaysia Perlis, 2011)
Access is limited to UniMAP community.